Second look PCNL for residual renal calculi: experience in Hospital Universiti Kebangsaan Malaysia - Ab Rashid, Islah Munjih; B, Badrulhisham; MZ, Zulkifli; JM, Nazri; S, Sritharan; Lee, BC (2005)
BACKGROUND Presence of residual calculi post PCNL is not rare. Due to the presence of residual calculi, patientm ight be subjectedt o a repeatP CNL under generala naesthesiaw hich is not without the risk of increased morbidity. Second look PCNL might reduce the chanceo f a repeatP CNL and subsequentlyre ducet he risk of morbidityto the patient. AIM To audit retrospectivelyt he outcomeo f secondl ook PCNL in our centerf rom January 2003 to October 2005. MATERIALAND METHOD 33 patients underwent second look PCNL for residual stone in our center from January 2003 to October 2005.The records of each patient were traced and the data analysed. The stone clearance. tolerability of procedure, complications and operation time were the variables and outcome studied. RESULT Out of 33 patients, 4 achieved complete clearance, 8 almost complete clearance, and 13 partial clearancew hile only 4 patientsh ad unsuccessfusl econdl ook operation due to technical difficulties. In another 4 patients, the KUB x-rays were doubtful and second look operation confirmed the absence of stone in the pelvicalyceal system. There were no complications and the procedure well tolerated by all the patients. CONCLUSION Due to its advantagesa nd low morbidity, secondl ook PCNL shouldb e an alternative method of treatment for residual stones whenever indicated.